Trade Facilitation and Intra-Regional Trade in the East African Community: Evidence from Panel Data Analysis - Erick Mchuma; Issacs Kipruto Kemboi; Simeon Nganai (PT. Global World Scientific, 2026)
This research investigates the impact of trade facilitation initiatives on intra-regional trade dynamics within the East African Community (EAC) across the period from 2010 to 2024. Despite the EAC's progress towards regional integration, intra-regional trade continues to underperform relative to its potential a situation attributable to enduring procedural problems and institutional deficiencies. The study employed a random effects model to estimate the panel trade data from EAC member countries. The results reveal that export documentation costs, import clearance time and controlling corruption are positively and significantly associated with trade flows while import documentation costs and regulatory quality exert negative influence. Findings highlighted the need for policies that improve trade efficiency, simplify regulations, and promote institutional transparency to help integrate trade within the East African Community. East African Community member states ought to prioritize the streamlining and standardization of trade documentation especially concerning imports, to mitigate procedural barriers that impede cross-border commerce. Enhancing digital customs platforms and broadening the scope of electronic clearance systems can significantly improve processing efficiency and transparency. Furthermore, bolstering anti-corruption initiatives at border crossings is essential given that improved governance directly facilitates more seamless trade and diminishes unofficial expenses.